BET and BRAF inhibitors act synergistically against BRAF‐mutant melanoma. (11th May 2016) - Paoluzzi, Luca; Hanniford, Douglas; Sokolova, Elena; Osman, Iman; Darvishian, Farbod; Wang, Jinhua; Bradner, James E.; Hernando, Eva
Abstract: Despite major advances in the treatment of metastatic melanoma, treatment failure is still inevitable in most cases. Manipulation of key epigenetic regulators, including inhibition of Bromodomain and extra‐terminal domain (BET) family members impairs cell proliferation in vitro and tumor growth in vivo in different cancers, including melanoma. Here, we investigated the effect of combining the BET inhibitor JQ1 with the BRAF inhibitor Vemurafenib in in vitro and in vivo models of BRAF‐ mutant melanoma. We performed cytotoxicity and apoptosis assays, and a xenograft mouse model to determine the in vitro and in vivo efficacy of JQ1 in combination with Vemurafenib against BRAF‐ mutant melanoma cell lines. Further, to investigate the molecular mechanisms underlying the effects of combined treatment, we conducted antibody arrays of in vitro drug‐treated cell lines and RNA sequencing of drug‐treated xenograft tumors. The combination of JQ1 and Vemurafenib acted synergistically in BRAF ‐mutant cell lines, resulting in marked apoptosis in vitro, with upregulation of proapoptotic proteins. In vivo, combination treatment suppressed tumor growth and significantly improved survival compared to either drug alone. RNA sequencing of tumor tissues revealed almost four thousand genes that were uniquely modulated by the combination, with several anti‐apoptotic genes significantly down‐regulated. Collectively, our data provide a rationale for combined BET and BRAF inhibition as a novel strategy for the treatment of melanoma. Abstract : We believe that the combination of BRAF inhibitors with new epigenetic drugs such as Bromodomain and extraterminal domain (BET) inhibitors offers a unique chance for the development of novel treatment programs for challenging malignancies such as melanoma.